Influence of religion and spirituality on head and neck cancer patients and their caregivers: a protocol for a scoping review - Maheeka Seneviwickrama; Ruwan Jayasinghe; Kehinde Kazeem Kanmodi; Simon N. Rogers; Su Keill; Sakuntha Ratnapreya; Sriyani Ranasinghe; Sashini Shehana Denagamagei; Irosha Perera (Systematic Reviews)
Abstract Introduction Head and neck cancers (HNC) are devastating, thus imposing a negative impact on the appearance of an individual as well as vital activities such as eating, swallowing, speaking, and breathing. Therefore, HNC patients undergo distress, while their caregivers become overburdened. Religion and spirituality can be helpful for patients and their caregivers from diverse cultural backgrounds to cope with cancer. Though well established in palliative care, religion and spirituality are rarely incorporated into usual early oncological care. Despite the availability of heterogeneous literature examining the influence of religion and spirituality on cancer patients, there is notably limited research on this topic across the HNC trajectory. Therefore, this scoping review attempts to answer “What is the influence of religion or spirituality on HNC patients and their caregivers in different contexts?” and will map the evidence on the influence of religion and spirituality on HNC patients and their caregivers in different contexts including geographical areas, cultures, health care systems, and different study settings. Methods This scoping review was formulated using the guidelines of Joanna Briggs Institute (JBI) manual for evidence synthesis: scoping reviews and will be reported confirming to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR checklist). A comprehensive search strategy will include Embase, CINAHL, Scopus, and APA PsycINFO. The OPENGREU.EU and Google Scholar will be used as gray literature sources complimented by manual searches. Our eligibility criteria follow the population, concept, and context (PCC) framework. Patients aged ≥ 18 years diagnosed with HNC and their informal, nonpaid caregivers aged > 18 years will be included. The data will be extracted using piloted data extraction form on sociodemographic, disease-related, and treatment-related factors and outcomes, and the data will be analyzed through descriptive statistics and thematic analysis. The results will be narratively synthesized. Conclusions/discussion This review will aim to explore existing literature and summarize the findings of studies that examine the influence of religion and spirituality among HNC patients and their caregivers and vice versa over a range of physical, psychological, and social outcomes including quality of life. We also aim to identify existing research gaps. The findings of this review would generate evidence to better inform health care providers in countries and cultures in the management of patients diagnosed with HNC in usual oncological care with due consideration to caregivers.